The Effect of Physical Exercises Using Different Styles for Developing Some Strength Types in National Center for Gifted in Soccer Aged (13 – 14) Years Old - Neamah, Hayder; Altay, Usama (Journal of Physical Education, 2020)
The Importance of the research was in establishing a strong physical base by designing and applying exercises with different styles that aim at developing strength types in soccer players aged 13 – 14 years old. The problem of the research was in diagnosing weakness in all types of strength (concentric strength, explosive strength and speed strength). The aims of the research were to use exercises with different styles and identifying their effect on strength types. The researchers hypothesized statistical differences in favor of the post tests. The researchers used the experimental method. The sample was (142) soccer players aged 13 – 14 years old from the national center for gifted in soccer while the subjects were (19) players. The pretests were followed by the main experiment for (16) weeks with two training sessions for (18 – 24) minutes. The results showed significant differences in favor of the posttests. The researchers concluded that the applied exercises positively developed different types of strength on soccer players aged 13 – 14 years old.